Uso de las plantas medicinales en el tratamiento de enfermedades respiratorias en el sector 9 de octubre Cantón Puebloviejo de la Provincia de Los Ríos del periodo octubre 2019 – marzo 2020. - Ronquillo Romero, Karicdis Alexandra (2020)
This research project includes a determinable work of scientific articles and research on the use of medicinal plants in the treatment of respiratory diseases, with the main objective being to identify the plants used by the people of Sector 9 de Octubre of the Pueblo Canton of the Province of the Rivers. In the data collection stage, the investigative method that will be used for the Deductive-Analysis which are clearly explained in the next chapters. Regarding the results of the investigation carried out, it was observed that the inhabitants of the sector October 9 in the period that was selected October 2019 to March 2020, the plants most used by the inhabitants of the sector were identified were the Air Sheet with a percentage of 42% and Eucalyptus with 33%, we could also determine which plants they use do so with curative and preventive fines. A guide to medicinal plants was proposed to treat respiratory diseases in order to be used and applied appropriately to these botanical species; We gave talks about the use and benefit of each plant in order to enrich people's knowledge. The most common respiratory conditions were Flu and Cough due to the winter seasons, which is where these pathologies are due to the conditions in which the residents of the October 9 sector are. Once this research project was completed, we could see that the inhabitants of the sector obtained more information about the plants and the proper use that should be given to them.